Transforming Islamic Religious Education: Building Critical Thinking and Religious Tolerance - Ubaidilah, Cecep; Ahmad fathurahman, Asep; Setiawan, Marwan (Yayasan Mentari Madani, 2024)
In an increasingly complex social, cultural, and global reality, the transformation of Islamic religious education becomes imperative to equip students with the necessary skills and attitudes to navigate modern challenges. Traditional approaches to Islamic religious education may no longer suffice in addressing contemporary issues such as radicalism, extremism, and religious intolerance. This paper explores the significance of transforming Islamic religious education to cultivate critical thinking and religious tolerance among students. By emphasizing active, reflective, and dialogical learning approaches, educators encourage students to question, analyze, and reflect on Islamic teachings critically. Moreover, through a deep understanding of diversity principles within Islam and interfaith dialogue, Islamic religious education plays a crucial role in fostering religious tolerance. However, implementing this transformation faces challenges, including inadequate teacher training, institutional support, and curriculum constraints. Addressing these challenges requires investments in human resource development, financial support for diverse curriculum development, and the promotion of collaboration among educational institutions with different religious backgrounds. Only through concerted efforts can Islamic religious education contribute positively to building critical thinking and religious tolerance among students, preparing them to become integral members of harmonious and inclusive societies.